Nonlinear Adjustment Of Real Exchange Rates Towards Purchasing Power Parity And The Asian Financial Crisis - Liew, Venus Khim-Sen; Ahmad Zubaidi, Baharumshah; Lim, Kian-Ping (Universiti Malaysia Sarawak (UNIMAS), 2005)
This paper investigates the underlying dynamics of the adjustment process of the deviations of two selected ASEAN exchange rates from long-run equilibrium level as suggested by the well-known purchasing power parity (PPP) hypothesis. To accomplish this task, we estimate the standard linearity test statistics as suggested by Lukkonen, Saikkonen and Teräsvirta (1988), which has power against the Exponential Smooth Transition Autoregressive (ESTAR) model. Using quarterly data series, our results reveal that both the bilateral Indonesian repiah-U.S. dollar (IDR/USD) and Singaporean dollar-U.S. dollar (SGD/USD) adjust nonlinearly towards the PPP equilibrium level. Another interesting insight from this study is the relationship between the adjustment process and the recent Asian Financial Crisis. The results reveal that an exchange rate with high speed of adjustment such as the bilateral SGD/USD tends to be less adversely affected by the crisis. On the other hand, for an exchange rate characterised by a low speed of adjustment as in the case of IDR/USD, most of the deviations are left unadjusted or only partially adjusted. Until one stage whereby the accumulated deviations are no longer sustainable, tremendous market correction in action, leading to a tremendous plunge in value as we observed in the IDR/USD during the 1997 crisis.